FAKTOR-FAKTOR YANG BERKAITAN DENGAN PERILAKU KEWIRAUSAHAAN PEDAGANG KAKILIMA (Kasus Pedagang Kakilima Pemakai gerobak Usaha Makanan Di Kota Bogor) - Sapar Sapar; Richard W.E. Lumintang; Djoko Susanto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
The study was carried out in Bogor in June through September 2005. The objectives of the study were : (1) to identify the external and internal factors of street food peddler, (2) to identify entrepreneurship behavior of the street food peddler, and (3) to analyze the correlation between the internal and the external factors and entrepreneurship behavior of the street food peddler. The study was a descriptive correlational method. Data were collected using a structured questionnaire. Data were analyzed using Spearman Rank correlation. The results of the study showed that: (1) The internal and the external factors were significantly correlated with the street food peddler entrepreneurship behavior, (2) The street food peddler entrepreneurship behavior were categorized high and medium.